Bioarchaeological insights into disability: Skeletal dysplasia from the Iron Age northern China. (24th November 2021) - Zhou, Yawei; Lu, Yiping; He, Jianing; Li, Ziyi; Zhang, Xiangyu; Zhang, Qun; Yeh, Hui‐yuan
Abstract: Skeletal dysplasia is mainly caused by genetic mutations or endocrine abnormality. In this study, a case of disproportionate dwarfism from the Iron Age Beishenjiaqiao cemetery in Xi'an, China is analyzed from the perspective of bioarchaeology. The individual shows disproportionately short stature, with reduced long‐bone diaphyseal length especially of both humeri, unfused proximal humerus epiphyses, abnormal development of the shoulder and hip joints, left femoral head necrosis, and unusually gracile left femur and tibia shaft, demonstrating limited mobility and labor capacity. Hypothyroidism, pseudoachondroplasia, and multiple epiphyseal dysplasia are the most likely possible diagnoses although there are other possibilities. By combining the archaeological evidences and historical records, it is speculated that this individual lived a normal life and was well treated during her lifetime. Overall, this rare case concerning dwarfism not only enriches our knowledge of skeletal dysplasia among ancient Chinese in northern China but also demonstrates the humanitarian attitude of ancient society toward the disability.